La biopiratería en los recursos genéticos y su incidencia en los derechos de autor de los conocimientos ancestrales y sus recursos biológicos, dentro del margen del derecho comparado en los países de Colombia y Perú - Camacho Cuenca, Edgar Daniel (2024)
The present integration curricular work is entitled “Biopiracy in genetic resources and its impact on the copyright of ancestral knowledge and its biological resources, within the scope of the comparative law of Colombia and Peru”, The interest in investigating and conducting an analysis is due to the fact that there is evidence of the violation of copyrights within their ancestral knowledge, genetic and biological resources within the biodiversity as multinationals, scientists, research centers, etc. illegally and illegitimately appropriate Ecuadorian nature. The biopiracy is the illegal, irregular or inequitable access, use and exploitation of biological resources and their derivatives, as well as of the traditional knowledge of indigenous peoples associated with them, especially through the improper use of intellectual property, infringing exclusive rights over them, In recent years, resources such as ayahuasca, maca or quinoa and the traditional knowledge associated with them have become part of inventions legally protected by patents or other intellectual property rights, without recognition of their origin. This misappropriation or illegal appropriation of genetic resources, seeds and traditional knowledge of indigenous peoples is referred to as biopiracy. On the other hand, comparative legislation such as that of Peru and Colombia has well-founded expectations to ensure that access to their resources and the use of the traditional knowledge of their communities is carried out on a basis of equity and justice, complying with the existing regulatory frameworks.